TATWIR AL WASAAIL AT TAKLIMIYYAH AL ARABIYYAH ‘ALAA ASAS WORDWALL FII MADRASATI AL YUSRIYAH TSANAWIYAH - Muhammad Maulana; Muhammad Taufiq (El-Tsaqafah : Jurnal Jurusan PBA, 2023)
This research aims to assist the process of teaching the Arabic language, which is able to raise students' interest in learning the Arabic language. This research uses the research and development method, with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research developed educational tools on websites, which are Wordwall tools. Wordwall methods applied to students in learning Arabic succeeded in increasing students' interest in learning Arabic as evidenced by the responses of 32 students with an average score of 90%. These Wordwall tools also succeeded in validating the Arabic language teacher response questionnaires, materials, and materials, the result from the media experts got an average score of 83%, the materials experts 84% ??and the Arabic teacher response questionnaires 90%. With this guide, Wordwall media is very good as a tool in the Arabic learning media in the Yusriya High School.